Genetic analysis of roe deer (Capreolus capreolus L.) using DNA markers - Pūraitė, Irma; Paulauskas, Algimantas; Sruoga, Aniolas (2014)
DNA markers play a major role in genetic analysis of mammals. The aim of this study was to assess the genetic structure of roe deer in Lithuania using microsatellite and D-loop sequences analysis. Seven microsattelite derived from rein deer (Rangifer tarandus) with published primer sequences were used. Total number of alleles per locus varied from 2 to 9 and number of effective alleles varied from 2,0 to 7,5. Analysis of molecular variance (AMOVA) showed that genetic diversity of the populations yielded 79 % of the total genetic diversity and among populations 21 % of the total genetic diversity. Mitochondrial DNA was amplified using L-Pro and H-493 primers, which amplify a 436 bp fragment from the first hypervariable domain of the mtDNA control region. Six haplotypes and two haplogroups were identified in population of roe deer in Lithuania. A total 41 variable sites were detected in mtDNA variable region. H2, H3, H4, H5 and H6 haplotypes were specific in roe deer from Lithuania. Haplotype diversity Hd = 0.854 and nucleotide diversity Pi = 0.01981 were calculated. Results of DNA markers analysis revealed high level molecular genetic variation in roe deer population in Lithuania.